Performance audit analysis done by the national audit office of Lithuania - Stankevič, Evelina (Buhalterinės apskaitos teorija ir praktika, 2013)
Performance audit is identified as one of the relatively newly developed type of audit, in which the reactivation of research was observed only in the twentieth century. The need to analyse and develop a new type of audit is associated with the changes occurred and on-going in business and public administration, and also with other factors such as social, political, economic, technological changes and other.Evaluation and improvement of entities becomes more and more important and substantial in accordance with the development of a new approach in public sector, public administration and asset management. The definition and implementation of the new public management paradigm has influenced this process as well. In light of new circumstances the importance of evaluation performance audit is growing rapidly.This paper briefly summarizes and evaluates the theoretical basis of the performance audit, the reasons for the performance audit examination, importance of improvement and adaptation of analysis. Particular attention was given to performance audit analysis which was done by the National Audit Office of Lithuania. The purpose of the paper is to examine performance reports published by the National Audit Office of Lithuania and statistic data for 2010-2012. Survey was conducted in accordance with the composition of performance audits operational process of auditing and the performance audits timeframe trend.The study revealed that in 2010 year was performed 41 percent of all conducted performance audits in 2010-2012 year, while in 2011 and 2012 – 29,5 percent. It was also found that over 54 percent of performance audits were conducted with pre-and main studies. Mainly performance audit conducted with pre-and main studies were in 2012 year and reached 68,2 percent from all conducted performance audits that year. The lowest rate was in 2010 year and it reached 46,7 percent from all conducted performance audits. Analysis of the performance audits conducted with pre-and main stages according to duration of each stage showed that time off each stage fulfilment has grown during the period of 2010-2012. Analysis of pre-stage period showed that it has increased by 8,3 percent from 2010 to 2012, without consideration of the reporting time. The reporting time after a preliminary investigation grew by 14,3 percent, main study fulfilment period increased by 26,8 percent, and reporting time after the main study – 2,6 percent.
Keywords: performance audit; elements of performance audit; analysis of performance audits; duration of performance audits